Privilege Escalation Techniques - Ahmed, Alexis (Packt Publishing, 2021)
Enumerate and exploit Linux or Windows systems and escalate your privileges to the highest level Key Features Discover a range of techniques to escalate privileges on Windows and Linux systems Understand the key differences between Windows and Linux privilege escalation Explore unique exploitation challenges in each chapter provided in the form of pre-built VMs Book Description Privilege escalation is a crucial step in the exploitation life cycle of a penetration tester. It helps penetration testers to set up persistence and facilitates lateral movement. This book is one of a kind, covering a range of privilege escalation techniques and tools for both Windows and Linux systems. The book uses virtual environments that you can download to test and run tools and techniques. Each chapter will feature an exploitation challenge in the form of pre-built virtual machines (VMs). As you progress, you will learn how to enumerate and exploit a target Linux or Windows system. This privilege escalation book then demonstrates how you can escalate your privileges to the highest level. By the end of this book, you will have gained the skills you need to be able to perform local kernel exploits, escalate privileges through vulnerabilities in services, maintain persistence, and enumerate information from the target such as passwords and password hashes. What you will learn Understand the privilege escalation process and set up a pentesting lab Gain an initial foothold on the system Perform local enumeration on target systems Exploit kernel vulnerabilities on Windows and Linux systems Perform privilege escalation through password looting and finding stored credentials Get to grips with performing impersonation attacks Exploit Windows services such as the secondary logon handle service to escalate Windows privileges Escalate Linux privileges by exploiting scheduled tasks and SUID binaries Who this book is for This Windows and Linux privilege escalation book is for intermediate-level cybersecurity students and pentesters who are interested in learning how to perform various privilege escalation techniques on Windows and Linux systems, which includes exploiting bugs, design flaws, and more. An intermediate-level understanding of Windows and Linux systems along with fundamental cybersecurity knowledge is expected.